Long-term elasticity in the continental lithosphere ; modelling the Aden Ridge propagation and the Anatolian extrusion process - Hubert-Ferrari, Aurélia; Armijo, Rolando; King, Geoffrey; Manighetti, Isabelle; Meyer, Bertrand; Tapponnier, Paul (My University, 2003)
The evolution of the Gulf of Aden and the Anatolian Fault systems are modelled using the principles of elastic fracture mechanics usually applied to smaller scale cracks or faults. The lithosphere is treated as a plate, and simple boundary conditions are applied that correspond to the known plate boundary geometry and slip vectors. The models provide a simple explanation for many observed geological features. For the Gulf of Aden the model predicts why the ridge propagated from east to west from the Owen Fracture Zone towards the Afar and the overall form of its path. The smaller en echelon offsets can be explained by upward propagation from the initially created mantle dyke while the larger ones may be attributed to the propagating rupture interacting with pre-existing structures. For Anatolia the modelling suggests that the East Anatolian Fault was created before the North Anatolian Fault could form. Once both faults were formed however, activity could switch between them. The time scales over which this should take place are not known, but evidence for switching can be found in the historical seismicity. For Aden and Anatolia pre-existing structures or inhomogeneous stress fields left from earlier orogenic events have modified the processes of propagation and without an understanding of the existence of such features the propagation processes cannot be fully understood. Furthermore a propagating fault can extend into an active region where it would not have initiated. The North Anatolian Fault encountered slow but active extension when it entered the Aegean about 5 Ma and the stress field associated with the extending fault has progressively modified Aegean extension. In the central Aegean activity has been reduced while to the north-west on features such as the Gulfs of Evvia and Corinth activity has been increased. The field observation that major structures propagate and the success of simple elastic models suggest that the continental crust behaves in an elastic-brittle or elastic-plastic fashion even though laboratory tests may be interpreted to suggest viscous behaviour. There are major problems in scaling from the behaviour of small homogeneous samples to the large heterogeneous mantle and large-scale observations should be treated more seriously than extrapolations of the behaviour of laboratory experiments over many orders of magnitude in space and time. The retention of long-term elasticity and localised failure suggests a similar gross rheology for the oceanic and continental lithospheres. Even though it is incorrect to attribute differences in behaviour to the former being rigid (i.e. elastic) and the latter viscous, oceanic and continental lithosphere behave in different ways. Unlike oceanic crust, continental crust is buoyant and cannot be simply created or destroyed. The process of thickening or thinning works against gravity preventing large displacements on extensional or contractional features in the upper mantle. The equivalents of ridge or subduction systems are suppressed before they can accommodate large displacements and activity must shift elsewhere. On the other hand, strike-slip boundaries and extrusion processes are favoured.
Keywords: Anatolian Fault; continental deformation; fault propagation; Gulf of Aden